Behavioral Response of a Rehabilitated Siamang (Symphalangus syn-dactylus) to Environmental Enrichment at the Punti Kayu Rehabilitation Center, Indonesia - Kamila Alawiyah; Dini Oktalia Yulius; Selly Novrianti (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2026)
Populations of the Siamang (Symphalangus syndactylus) are declining due to habitat loss and illegal exploitation, highlighting the need for effective conservation strategies. Rehabilitation and reintroduction programs are important efforts, but their success depends on the behavioral readiness of individuals. Therefore, this study aimed to assess activity budgets, vertical space utilization, and behavioral responses to environmental enrichment in a rehabilitated siamang candidate for release. Behavioral observations were conducted using a scan sampling method during two periods, before and after the implementation of environmental enrichment. The enrichment consisted of woven palm leaf devices filled with fruits and vegetables placed at elevated positions to stimulate natural foraging and locomotion behaviors. Observed behaviors included feeding, locomotion, resting, grooming, social interaction, and enclosure strata use, which were analyzed quantitatively based on frequency and percentage. The results showed that environmental enrichment influenced behavioral patterns and activity distribution. Active behaviors increased from 57.67% before enrichment to 72.6% after enrichment, while resting behavior decreased from 42.33% to 27.4%. Social interaction increased notably, and locomotion remained a dominant activity. Vertical space utilization also shifted, with the use of the upper stratum increasing from 66.0% to 86.1%, while the lower stratum was no longer utilized after enrichment. In conclusion, environmental enrichment enhances behavioral competence in rehabilitated siamangs by promoting active behaviors and encouraging the use of upper canopy space, supporting their readiness for release.